Development and implementation of an energy management immote system (iot) for the Private University of Tacna - Acero Catacora, Christian (2020)
A good management of energy consumption in luminaire is subject to an application of techniques or technologies that help to automate its use more effectively. In this case, we speak of an Inmotic System of the Internet of Things, a Place of a Service, a Presence of a System, an Intelligent Building or an Intelligent Building, which has the objective of the integrated and automated management of almost all the functionalities of a building such as electricity, lighting, air conditioning, etc. It is also an Internet of Things system for the connectivity and the management of the devices for the control of the intensity of the luminosity according to the movement and the level of natural light in an environment, acting autonomously or controlled from a web application This means a reduction of 40% in the energy expenditure in the luminaire, which meets one of the criteria of an intelligent building.